Design and Development of Sustainable Lean Manufacturing Using Interpretive Structural Model (ISM) Approach.: Developing a Framework for Sustainable Lean Implementation (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The survival of any organization depends upon its competitive edge. Even though Lean is one of the most powerful quality improvement methodologies, nearly two-thirds of the Lean implementations results in failures and less than one-fifth of those implemented have sustained results. One of the most significant tasks of top management is to identify, understand and deploy the significant Lean practices like quality circle, Kanban, Just-in-time purchasing, etc. The term ‘parameters’ is used to make groups of inter-related and internally consistent Lean practices. Eight significant Lean practice parameters have been identified based on literature reviewed and opinion of the experts. The order of execution of Lean practice parameters is very important. Lean practitioners must be able to understand the interrelationship between these practice parameters. The objective of this paper is to develop framework for sustainable Lean implementation using interpretive structural modelling approach. The main objectives of this paper areTo identify and prioritize the Lean practices parameters►To discover and analyse the interaction among identified Lean practices parameters using ISM and►To develop a framework for sustainable Lean implementationIn this research, study factors are the Lean practices bundles for successful Lean implementation. Authors have identified twelve significant Lean practices parameters from literature review and opinion of the experts.